2019
DOI: 10.3390/electronics8030317
|View full text |Cite
|
Sign up to set email alerts
|

Network-Oriented Real-Time Embedded System Considering Synchronous Joint Space Motion for an Omnidirectional Mobile Robot

Abstract: This paper proposes a real-time embedded system for joint space control of omnidirectional mobile robots. Actuators driving an omnidirectional mobile robot are connected in a line topology which requires synchronization to move simultaneously in translation and rotation. We employ EtherCAT, a real-time Ethernet network, to control servo controllers for the mobile robot. The first part of this study focuses on the design of a low-cost embedded system utilizing an open-source EtherCAT master. Although satisfying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As EtherCAT is becoming the standard network protocol in ICSs, an open source EtherCAT master, IgH Etherlab, was stacked on top of Xenomai to establish a connection with an actual industrial network. In the literature, numerous studies are present related to the implementation and performance of EtherCAT on different variations of real-time Linux [25,32,33]. To our knowledge, this work is the first attempt on implementing EtherCAT on an Android-based embedded system.…”
Section: Software Architercturementioning
confidence: 99%
See 3 more Smart Citations
“…As EtherCAT is becoming the standard network protocol in ICSs, an open source EtherCAT master, IgH Etherlab, was stacked on top of Xenomai to establish a connection with an actual industrial network. In the literature, numerous studies are present related to the implementation and performance of EtherCAT on different variations of real-time Linux [25,32,33]. To our knowledge, this work is the first attempt on implementing EtherCAT on an Android-based embedded system.…”
Section: Software Architercturementioning
confidence: 99%
“…An important metric to evaluate the real-time performance of the system is the periodicity and response times of the RT task. Conducting the same experiment in the previous section, the periodicity and response times of the RT task were measured following the detailed evaluation procedures presented in our previous works [25,36]. The periodicity and response time of an RT task determines whether the task is schedulable or not.…”
Section: Real-time Performancementioning
confidence: 99%
See 2 more Smart Citations
“…T period represents the actual time that it takes for one cycle of the task. Its relationship with the jitter is defined by the following equation [32,33]: The results show that the task with the highest priority had the best performance with the lowest deviation to the statistical average of period and jitter. Therefore, it is confirmed that the AUTOSAR OS performed scheduling according to priority and satisfied periodicity.…”
Section: Real-time Performancementioning
confidence: 99%